Homelessness and Incarceration: An Examination of Barriers to Misdemeanor Resolution for the Homeless - Herzog, Joseph R.; Lee, Chang-Bae; Sansone, Frank A.; Olson, Mark (International Journal of Criminology and Sociology, 2012)
The relationship between homelessness and crime has been investigated in few studies despite the implications of prior offenses and incarceration on job seekers. This study examined the relationship among homelessness, misdemeanors, incarceration, and misdemeanor resolution. Factors hindering misdemeanor resolution were explored by surveying participants at two Veterans Administration (VA) Stand Downs (n=186). The sample includes the primary service population of homeless veterans and other homeless persons. Respondents reported on factors perceived as limiting them from resolving misdemeanors, along with socio-demographic, homeless status, misdemeanor, and incarceration data. Factor Analysis yielded three factors as barriers that have implications for social work practice.